Analysis of Energy Flow in a Mid-Sized Electric Passenger Vehicle in Urban Driving Conditions - An, Youngkuk; Yang, Byeonggyu; Park, Jinil; Lee, Jonghwa; Park, Kyoungseok (World Electric Vehicle Journal, 2023)
Because of emissions of exhaust gases, global warming is proceeding, and air pollution has increased. Thus, many countries are manufacturing eco-friendly vehicles, including electric vehicles. However, the range of electric vehicles is less than the range of internal combustion engine vehicles, so electric vehicle production is being disrupted. Thus, it is necessary to analyze the energy flow of electric vehicles. Therefore, to analyze energy flow of electric vehicles, this study suggested an energy flow structure first, then modeled the energy flow of the vehicle, dividing it into battery, inverter and motor, reduction gear and differential, and wheel parts. This study selected a test vehicle, drove in urban driving conditions and measured data. Then, this study calculated energy flow using MATLAB/SIMULINK in real time, and calculated and analyzed energy loss of each of the vehicle’s parts using the calculated data.
Keywords: Driving conditions; Eco-friendly; Energy flow; Energy flow analysis; EV; Internal combustion engine vehicles; Modeling; Passengers vehicles; Reduction gear; UDDS; energy flow; energy flow analysis; energy loss; EV; modeling; UDDS